2006
DOI: 10.1159/000094845
|View full text |Cite
|
Sign up to set email alerts
|

New Radiofrequency Coil Integrated with a Stereotactic Frame for Intraoperative MRI-Controlled Stereotactically Guided Brain Surgery

Abstract: Mislocalization errors caused by MR image distortions or brain shift are one of the main causes of complications after stereotactically guided neurosurgical procedures. A special device, which could ameliorate such effects and provide intraoperative acquisition of MR images of sufficient diagnostic accuracy, was developed. It is composed of a radiofrequency receiver coil integrated with a modified Komai stereotactic frame and a Sugita four-pin head holder. Clinical testing revealed that the use of the device d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Once the position of the patient and the head is rigidly stabilized in a frame the coordinates of the anatomical control points on the head are registered to virtual image anatomy in the image space. The locating probe is used to establish the salient anatomy landmarks to navigate with infra-red or radio frequency detection system(H. Taniguchi et al, 2006). The Rotitome-G has electromagnetic solenoids built into the instrument for tumour-space navigation.…”
Section: Rotitome-g Instrument Placement and Practice Of The Hsg-amoe...mentioning
confidence: 99%
“…Once the position of the patient and the head is rigidly stabilized in a frame the coordinates of the anatomical control points on the head are registered to virtual image anatomy in the image space. The locating probe is used to establish the salient anatomy landmarks to navigate with infra-red or radio frequency detection system(H. Taniguchi et al, 2006). The Rotitome-G has electromagnetic solenoids built into the instrument for tumour-space navigation.…”
Section: Rotitome-g Instrument Placement and Practice Of The Hsg-amoe...mentioning
confidence: 99%
“…22,23,32,33,39,72,77 Kameyama et al reported the largest group, consisting of 25 patients, of whom 19 (76%) had seizure remission. As seen in the SRS group, substantial improvements in behavior also occurred.…”
Section: Hypothalamic Hamartomasmentioning
confidence: 99%
“…It provides an opportunity to perform MRI investigations with minimal distortion artifacts and maximum structure contrasting in any plane irrespectively to the orientation of the object, which allows fi xation of the patient ' s head in the most desirable position for tumor removal. Integration of the head-holder coil with a modifi ed Komai stereotactic frame [14] permits us to perform stereotactically guided surgical procedures under the control of iMRI ( ᭹ ᭤ Fig. 3 ).…”
Section: Intraoperative Mrimentioning
confidence: 99%